Caracterização físico-química, energética e sensorial de hidromel - Brunelli, Luciana Trevisan [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Mead is a good income option for honey producers (value added), allowing the development of a commercially little known drink in several countries, but it has great commercial potential. The objective of this work was to produce and analyze physicochemical and sensory fermented honey produced from the combination of three types of honey (eucalyptus, orange and sylvan) and different soluble solids concentrations in the initial must (20, 30 and 40 ºBrix). The experimental design was completely randomized with nine treatments and three repetitions, totaling 27 experimental units. After dilution of the honey, inoculation was carried out with dry yeast. Fermentation took place at room temperature (18-25º C) and monitored daily until the stabilization of the soluble solids content (ºBrix). After the end of the fermentation drawing off a was made. The fermentation was held at room temperature (18-22ºC). After this period, the first racking was made and fermented beverage remained at rest for 30 days. In the second separation, beverages were bottled in green glass bottles of 750 ml capacity. The meads were analyzed for pH, total, volatile and fixed acidity, alcohol content, total reducing sugars (TRS), dry extract, reduced dry extract, color and turbidity. Sensory analysis was made by acceptance testing - hedonic scale. The statistical analysis (ANOVA) for physicochemical and sensory analysis was done by F test and the treatment means compared by Tukey test at 5% probability. The increase in the proportion of honey in the formulation interferes in physicochemical and sensory parameters of meads. Beverages prepared with higher concentrations of raw material (honey) have higher acceptability.

O objetivo desse trabalho foi produzir e analisar físico-química e sensorialmente os fermentados de mel elaborados a partir da combinação de três tipos de mel (eucalipto, laranjeira e silvestre) e diferentes concentrações de sólidos solúveis no mosto inicial (20, 30 e 40 ºBrix). Após a diluição do mel, a inoculação foi realizada com levedura seca. A fermentação ocorreu em temperatura ambiente e acompanhada diariamente até a estabilização do teor de sólidos solúveis (ºBrix). Após o final da fermentação, foi feita a descuba. Os fermentados foram deixados em repouso à temperatura ambiente. Depois desse período, foi realizada a primeira trasfega, os fermentados permaneceram em repouso por 30 dias. Na segunda trasfega as bebidas foram acondicionadas em garrafas de vidro verde. Os hidroméis foram analisados quanto aos valores de pH, acidez total, volátil e fixa, teor alcoólico, açúcares totais, extrato seco, extrato seco reduzido, cor e turbidez. A análise sensorial foi por teste de aceitação (escala hedônica). Os resultados das análises físico-químicas dos mostos e dos hidroméis foram expressos por meio de média e desvio padrão, e foram submetidos à análise de variância (ANOVA) e as médias comparadas estatisticamente pelo teste de Tukey, ao nível de 5% de probabilidade. Os teores alcoólicos dos hidroméis variaram entre 10,46 a 14,36% v/v. O aumento da proporção de mel na formulação interfere nos parâmetros físico-químicos e sensoriais dos hidroméis. Quanto maior a quantidade de mel na formulação das bebidas (20, 30 e 40 ºBrix,), maiores foram os teores de açucares redutores, acidez total, extrato seco, extrato seco reduzido e tubidez. Dentro das condições em que foram conduzidos os testes experimentais, os hidroméis obtidos a partir de mel de laranjeira, eucalipto e silvestre, e três proporções de mel (20, 30 e 40 º ºBrix) na formulação ...
Physicochemical and sensory characterization of meads made with diferente types of honey
Keywords: Bebidas alcoólicas; Mel como alimento; Avaliação sensorial; Mel - Análise; Saccharomyces cerevisiae